Applying the CIPP Model to Assess the Impact of the Tahfidz Class Program on Quranic Retention - Abshor, Muhammad Ulil; Wafiati, Ifadatul; Sorfina, Nur Sabrina; Ma’arif , Samsul (Journal of Islamic Education Management Research, 2024)
Purpose – This study aims to evaluate the effectiveness of the Tahfidz Class Program at MTs Negeri 1 Yogyakarta in improving students' Quran memorization by applying the CIPP (Context, Input, Process, Product) evaluation model. Design/methods– The research adopts a qualitative descriptive approach to provide an in-depth understanding of the program's implementation and outcomes. Data collection methods included structured interviews with program stakeholders, direct observations of program activities, and analysis of institutional records. The CIPP model served as the analytical framework, with data analyzed using the descriptive model by Miles, Huberman, and Saldana, encompassing data condensation, data display, and conclusion drawing. Triangulation of sources was employed to ensure validity and reliability. Findings – The program aligns effectively with institutional goals and employs sufficient resources to enhance Quran memorization. The tikrar method significantly strengthens students' retention of Quranic verses. However, only 20% of participants achieved the target of memorizing four chapters, indicating room for improvement in teaching strategies and resource optimization. The findings also highlight the program's role in fostering both religious and academic excellence, though challenges remain in scaling these successes. Research implications/limitations – The study's scope is limited to a single institution, and its reliance on qualitative data may affect the generalizability of findings. Further research should explore broader implementations across diverse educational settings and examine innovative strategies for enhancing Quran memorization. Practical implications – The study provides actionable insights for improving the Tahfidz Class Program, including better resource allocation, refined teaching methods, and clearer target-setting mechanisms. These findings can inform similar programs in other institutions seeking to balance religious and academic education. Originality/value – This research offers a comprehensive evaluation of a specialized Quran memorization program using the CIPP model, demonstrating its applicability in educational program assessments. It contributes valuable insights into the integration of systematic evaluation frameworks in enhancing both the efficiency and impact of religious education programs.